Calculation of Production Cost in Determining the Selling Price in Bang Halim's Tofu Business - Pipin Pipin; Mukhammad Idrus; Hajrah Hamzah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study analyzes the calculation of the cost of goods manufactured (COGM) in determining the selling price of Bang Halim’s tofu business and identifies the supporting and inhibiting factors affecting this calculation. Data were collected through observation, interviews, and document analysis. One production run produces one talang containing 300 pieces (1 × 1.2 meters), using 5 kg of soybeans costing Rp50,000 and five workers paid Rp50,000 each per production run. Based on Bang Halim’s calculation, the COGM is Rp333.34 per piece, Rp100,002 per production run, and Rp45,000,900 per month. Using the full costing method, which includes raw material costs, direct labor costs, and factory overhead costs of Rp1,209,250, the calculated COGM is Rp4,030 per piece, Rp1,209,000 per production run, and Rp544,050,000 for November 2024. Bang Halim set the selling price at Rp500 per piece and Rp150,000 per talang, while the cost-plus pricing method with a 20% profit margin (Rp806) resulted in a selling price of Rp4,836 per piece, Rp1,450,800 per production run, and Rp652,860,000 per month with a profit margin of Rp108,810,000. The main supporting factor is the high quality of raw materials, while the inhibiting factor is limited knowledge of cost components, leading to inaccuracies in determining the cost of goods manufactured.